2021
DOI: 10.3390/biology10040273
|View full text |Cite
|
Sign up to set email alerts
|

Functional Monitoring after Trabeculectomy or XEN Microstent Implantation Using Spectral Domain Optical Coherence Tomography and Visual Field Indices—A Retrospective Comparative Cohort Study

Abstract: The aim of this study was to compare the efficacy of trabeculectomy (TE), single XEN microstent implantation (solo XEN) or combined XEN implantation and cataract surgery (combined XEN) in primary open-angle glaucoma cases, naïve to prior surgical treatment, using a monocentric retrospective comparative cohort study. Intraocular pressure (IOP) and the number of IOP-lowering drugs (Meds) were monitored during the first 24 months after surgery. Further disease progression was monitored using peripapillary retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
1
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 45 publications
3
15
1
7
Order By: Relevance
“…Additionally, the mean number of IOP-lowering medication was significantly reduced ( p < 0.01) in the two groups during follow-up. Similar to already published data, IOP reduction and higher success levels were more pronounced in eyes undergoing a TE compared to a XEN [ 19 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, the mean number of IOP-lowering medication was significantly reduced ( p < 0.01) in the two groups during follow-up. Similar to already published data, IOP reduction and higher success levels were more pronounced in eyes undergoing a TE compared to a XEN [ 19 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are in line with studies also reporting no changes of visual field function after glaucoma surgery [ 22 , 23 ]. Schargus et al also revealed stable visual field indices during the first 24 months after TE or XEN or XEN combined with cataract surgery in POAG eyes naïve to glaucoma surgery [ 20 ]. Kim et al demonstrated stable visual field indices although further statistically significant RNFL decrease during the first 12 months after TE or Ahmed valve implantation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…XEN45 implant eyes undergo needling more than TRAB surgery patients. [18][19][20][21][22][23][24][25][26] We performed needling for more patients in the XEN45 group (19%) compared with Kee et al 20 (1.5%) and Wagner et al 22 (16%); however, the incidence was less than that observed in other studies. 19,21,23,25,26 The needling rate published by studies with 36-month followup is 36.6%-55.4%.…”
Section: Discussionmentioning
confidence: 99%
“…29 The result agrees with that found in other studies about no difference in the postoperative NOAM between the XEN45 implant and TRAB surgery. [18][19][20][21][22][23][24] There are more limitations to this study. The retrospective design carries a risk of selection bias, the variability of treatment, IOP measurement, and loss of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation